Difference between a society of pure magic thought and a rationalistic thought - Helena Hernández Martínez; Juan Luis Miguel Díaz; Sonsoles Rodríguez de la Parra (Universidad de Alicante, 1999)
The difference between a society of pure magic thought and that of a rationalistic character is characterized by its humanity fundamentally based in science and sustained by science. As in any process implying an interpersonal relationship, the relation between nursing and the demanding users of health care, is of a reciprocal nature and as a consequence, full of sociological factors. In this work, we present the notion of mental health from a "social" perspective closely linked to those multi-cultural backgrounds whose different structures and functions contribute to the overall cultural system. A survey performed of mankind's philosophical and social thought regarding the concept of mental health and nursing care shows us their inter-relationship. The perception of mental illness has developed according to the evolution of social thought; and the nursing profession, part of this society, has also developed its thought and paradigm as a new discipline.